Hypoxia is not the primary mechanism contributing to exercise-induced proteinuria. Issue 1 (26th March 2020) - Joyce, Kelsley E; Delamere, John; Bradwell, Susie; Myers, Stephen David; Ashdown, Kimberly; Rue, Carla; Lucas, Samuel JE; Thomas, Owen D; Fountain, Amy; Edsell, Mark; Myers, Fiona; Malein, Will; et al.
Abstract : Introduction: Proteinuria increases at altitude and with exercise, potentially as a result of hypoxia. Using urinary alpha-1 acid glycoprotein (α1-AGP) levels as a sensitive marker of proteinuria, we examined the impact of relative hypoxia due to high altitude and blood pressure-lowering medication on post-exercise proteinuria. Methods: Twenty individuals were pair-matched for sex, age and ACE genotype. They completed maximal exercise tests once at sea level and twice at altitude (5035 m). Losartan (100 mg/day; angiotensin-receptor blocker) and placebo were randomly assigned within each pair 21 days before ascent. The first altitude exercise test was completed within 24–48 hours of arrival (each pair within ~1 hour). Acetazolamide (125 mg two times per day) was administrated immediately after this test for 48 hours until the second altitude exercise test. Results: With placebo, post-exercise α1-AGP levels were similar at sea level and altitude. Odds ratio (OR) for increased resting α1-AGP at altitude versus sea level was greater without losartan (2.16 times greater). At altitude, OR for reduced post-exercise α1-AGP (58% lower) was higher with losartan than placebo (2.25 times greater, p=0.059) despite similar pulse oximetry (SpO2 ) (p=0.95) between groups. Acetazolamide reduced post-exercise proteinuria by approximately threefold (9.3±9.7 vs 3.6±6.0 μg/min; p=0.025) although changes were not correlated (r=−0.10) with significant improvements in SpO2 (69.1%±4.5% vs 75.8%±3.8%; p=0.001). Discussion: Profound systemic hypoxia imposed by altitude does not result in greater post-exercise proteinuria than sea level. Losartan and acetazolamide may attenuate post-exercise proteinuria, however further research is warranted.